Room Temperature Self-Healable Natural Rubber - Sardi, Nur Syamsinar (Universiti Sains Malaysia, 2018)
Indeed to the properties of rubber which can sustain large deflection with little deformation. However, rubber still fail through fracture and fatigue over their service period. Emerging self-healing provides capability to arrest crack propagation at early stage and thereby preventing catastrophic failure. The aim of this work was to produce self-healing natural rubber that have capability to heal themselves spontaneously and autonomously at room temperature. Firstly, there were 2 stages implemented zinc thiolate was employed as self-healing agent with peroxide induced vulcanization to developed formation of covalent and reversible bonds with the natural rubber and exploited it as a potential self-healable materials. The amount of zinc thiolate was varied at four different levels (10 phr, 20 phr, 30 phr and 40 phr) to assess the optimum amount of zinc thiolate to achieve highest healing capability. Tensile properties of cured rubbers before and after healing process were measured using universal tensile tester to obtain healing efficiency of the materials. The results revealed that the developed self-healing natural rubber able to recover 60%-80% of its initial mechanical properties in a minutes and almost 100% in 10 minutes at room temperature without the aid of any external resources. It was also found that 30 phr zinc thiolate produced samples with highest healing capability. Evidence from Scanning Electron Microscopy (SEM) showed that the fracture area was fully recovered after the healing processed. Secondly, the effect of carbon black on the self-healing capability of the developed self-healing natural rubber was also investigated. The amount of carbon black was varied at three different levels (5 phr, 10 phr and 30 phr). Cure characteristics of the materials were measured using rheometer (MDR 2000). Tensile testing, crosslink density, elemental characterization and thermal analysis were carried out to investigate the healing efficiency of developed self-healing natural rubber filled with carbon black. The results revealed that addition of carbon black reduced the healing efficiency by 20%-30% but material with and without carbon black showed a stable thermal properties. SEM images showed that the fracture area was recovered after the healing process.